Silver(I)-Tazobactam Frameworks with Improved Antimicrobial Activity - Ferreira, Daniela R.; Alves, Paula C.; Kirillov, Alexander M.; Rijo, Patrícia; André, Vânia (Frontiers in Chemistry, 2022)
Tazobactam (TazoH) is a penicillinate sulfone β-lactamase inhibitor with negligible antimicrobial activity, commonly used with other antibiotics to provide an effective combination against many susceptible organisms expressing β-lactamases. Two novel Ag(I)-tazobactam frameworks ([Ag(I)-Tazo] and [Ag(I)-Tazo2]) prepared by mechanochemistry are presented herein as alternative forms to improve the antimicrobial activity of tazobactam by exploring synergistic effects with silver, being the first crystal structures reported of tazobactam coordinating to a metal site. The topological analysis of the 3D ([Ag(I)-Tazo]) and 2D+1D ([Ag(I)-Tazo2]) frameworks revealed underlying nets with the cbs (CrB self-dual) and decorated sql topologies, respectively. These novel frameworks are stable and show an enhanced antimicrobial activity when compared to tazobactam alone. Amongst the tested microorganisms, Pseudomonas aeruginosa is the most sensitive to tazobactam and the new compounds. This study thus unveils novel facets of tazobactam chemistry and opens up its application as a multifunctional linker for the design of antibiotic coordination frameworks and related materials.